Long-term Safety and Efficacy of Atazanavir-based Therapy in HIV-infected Infants, Children and Adolescents: The Pediatric AIDS Clinical Trials Group Protocol 1020A. Issue 2 (February 2015) - Rutstein, Richard M.; Samson, Pearl; Fenton, Terry; Fletcher, Courtney V.; Kiser, Jennifer J.; Mofenson, Lynne M.; Smith, Elizabeth; Graham, Bobbie; Mathew, Marina; Aldrovani, Grace
Abstract : Background: Atazanavir (ATV) is an attractive option for the treatment of Pediatric HIV infection, based on once-daily dosing and the availability of a formulation appropriate for younger children. Pediatric AIDS Clinical Trials Group 1020A was a phase I/II open label study of ATV (with/without ritonavir [RTV] boosting)-based treatment of HIV-infected children; here we report the long-term safety and virologic and immunologic responses. Methods: Antiretroviral-naïve and experienced children, ages 91 days to 21 years, with baseline plasma HIV RNA > 5000 copies/mL (cpm) were enrolled at sites in the United States and South Africa. Results: Of 195 children enrolled, 142 (73%) subjects received ATV-based regimens at the final protocol recommended dose; 58% were treatment naive. Overall, at week 24, 84/139 subjects (60.4%) and at week 48, 83/142 (58.5%) had HIV RNA ⩽ 400 cpm. At week 48, 69.5% of naïve and 43.3% of experienced subjects had HIV RNA ⩽ 400 cpm; median CD4 increase was 196.5 cells/mm 3 . The primary adverse event (AE) was increased serum bilirubin; 9% of subjects had levels ≥ 5.1 times upper limit of normal (ULN) and 1.4% noted jaundice. Three percent of subjects experienced grade 2 or 3 prolongation in PR or QTc intervals. At week 48, there was a 15% increase in total cholesterol (TC), with TC > 199 mg/dL increasing from 1% at baseline to 5.7%. Conclusions: Use of once-daily ATV, with/without RTV, was safe and well tolerated in children, with acceptable levels of viral suppression and CD4 count increase. The primary AE, as expected, was an increase in bilirubin levels. Abstract : Supplemental Digital Content is available in the text.